Konsep Pendidikan Imam AL-Ghazali - Azis, Abd (AL-BURHAN, 2023)
This study aims to uncover the reasons for Imam al-Ghazali's concern for education. This type of research is literature research, with a qualitative descriptive approach. The main data are taken from books and journals directly related to al-Ghazali's thoughts on education. Skunder data is taken from books and journals that have an indirect relationship with the main data. Data is collected by documentation techniques. After the data is collected, it is then analyzed using content analysis and inductive - deductive techniques. This study concluded that al-Ghazali's concern for education was more because al-Ghazali viewed education as something important and crucial for humans. There are three reasons for al-Ghazali to say that education is important and crucial. First, education has the duty to lead to man's primacy and approach to his God. Second, education produces scholars/educators/teachers, where scholars for al-Ghazali are guardians of human humanity. Third, the purpose of education, which is to draw closer to God and to achieve happiness in the world and in the end. Self-glory, being close to God, remaining in human glory, happy world and ultimate are the needs of every human being and all can only be attained through Education.